2020
DOI: 10.1155/2020/8836070
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Supersaturated Hydrogen-Rich Water Bathing on Biomarkers of Muscular Damage and Soreness Perception in Young Men Subjected to High-Intensity Eccentric Exercise

Abstract: High-intensity eccentric exercise can cause a delayed onset of muscle soreness (DOMS), a short-term condition characterized by muscle damage and tenderness that might hold up recovery and jeopardize exercise routine. Previous studies indicated that hydrogen-rich water (HRW) might be a helpful topical intervention to boost recovery in musculoskeletal medicine, yet no data are available concerning the effectiveness and safety of whole-body bathing with supersaturated HRW after DOMS-inducing exercise. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…Not only has hydrogen-rich water been shown to reduce oxidative stress injury and muscle fatigue in athletes through consumption, but studies show even the topical application of HRW has also been shown to reduce muscular pathological processes associated with oxidative stress [6]. High intensity exercise may result in delayed onset of muscle soreness (DOMS) which may jeopardize the athlete's exercise routine.…”
Section: Hydrogen-rich Application Water Transdermal Formsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only has hydrogen-rich water been shown to reduce oxidative stress injury and muscle fatigue in athletes through consumption, but studies show even the topical application of HRW has also been shown to reduce muscular pathological processes associated with oxidative stress [6]. High intensity exercise may result in delayed onset of muscle soreness (DOMS) which may jeopardize the athlete's exercise routine.…”
Section: Hydrogen-rich Application Water Transdermal Formsmentioning
confidence: 99%
“…High intensity exercise may result in delayed onset of muscle soreness (DOMS) which may jeopardize the athlete's exercise routine. In a randomized, double-blind, placebo-controlled crossover study in Serbia, six active, healthy male volunteers were exposed to DOMS-inducing eccentric leg press contractions and were immediately immersed up to the neck into a 200 L bathtub of supersaturated hydrogen-rich water (8mg of H2 per L) or placebo water (tap water with no hydrogen infusion) for 30 minutes [6]. The following blood markers were collected pre-exercise (baseline) and 24 hours after the exercise: creatine kinase (CK), lactate dehydrogenase (LDH), aspartate transaminase (AST), troponin, C-reactive protein (CRP), aldolase, myoglobin, and white blood cell (WBC) count.…”
Section: Hydrogen-rich Application Water Transdermal Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…Из выявленных нами тридцати публикаций девятнадцать цитируются в международной базе данных Scopus [1-4, 6-9, 11, [19][20][23][24][25][26][27][28][29][30] [20].…”
unclassified
“…Другой коллектив авторов значительно позже опубликовал статью о влияние купания в насыщенной ВВ на биомаркеры мышечного повреждения и восприятия болезненности у молодых мужчин, подвергнутых высокоинтенсивным эксцентрическим упражнениям [29].…”
unclassified